AKTIVITAS ANTIFUNGI EKSTRAK DAUN BELUNTAS, JAWER KOTOK, DAN SIRIH SERTA KOMBINASINYA TERHADAP Candida albicans - Yuniarni, Umi; Lukmayani, Yani (Universitas Ahmad Dahlan, 2016)
Piper betle, Coleus scutellarioides and Pluchea indica have been used empirically to overcome vaginal discharge and scientifically proven to inhibit the growth of Candida albicans. The goal of this research was to search for a combined extract with effective antimicrobial activity against Candida albicans. Single extract,combination of two and three extracts evaluated antimicrobial activity against Candida albicans using agar diffusion method. Inhibitory effect of Piper betle showed the greatest activity against Candida albicans compared to other single extract. Combination of Piper betle and Pluchea indica (26.57±0.56 mm) gave greater inhibition than two other combination extracts (Piper betle and Coleus scutellarioides (25.17±0.96 mm); Coleus scutellarioides and Pluchea indica (22.73±0.95 mm).The combination of Piper betle, Pluchea indica and Coleus scutellarioides gave inhibition of 27.53±1.10 mm. extracts did not give a better diameter compared to the betle extract.